Dialectics of knowing in education : transforming conventional practice into its opposite - Hooley, Neil (Abingdon, Oxon ; New York, NY : Routledge, 2018)
"Dialectics of Knowing strengthens the philosophical basis of formal education that has been weakened by neoliberalism over the past thirty years. It draws upon Greek philosophy that asked 'How should we live?' and European Enlightenment that considered 'What can we know?' to question today 'What does it mean to experience mind, to act, think and create ethically?' Focusing particularly on the notion of praxis and specific issues involving indigenous, feminist and practitioner knowing, this book will help scholars and practitioners to transform their education theories and practices in ways that encourage democracy, emancipation, social action, culture, inquiry and creativity" --
Poem : intellect -- Looking backwards, looking forwards -- Materialism and dialectics -- Science and humanities as praxis -- Intersubjective praxis -- Living with ethical conduct -- Looking inwards, looking outwards -- Subjectification : how we are -- Thinking about consciousness -- Language, thought and creativity -- Thinking in social and technological environments -- Looking to the earth, looking to the sky -- Indigenous philosophy and knowledge -- Feminism and education -- Bricolage : practitioner knowledge and research -- Dialectics of democracy, citizenry, knowing : a letter to those who would act and teach.
Includes bibliographical references and index.
AAL
Parama
Keywords: Education -- Philosophy; Democracy and education; Education -- Social aspects